Samorząd terytorialny w kontekście zasady pomocniczości w nauczaniu społecznym Kościoła katolickiego (Przegląd Religioznawczy – The Religious Studies Review, 2019)
In the modern world there is a growing reflection on the essence of the relationship between the state and society, which is regulated in according to the principle of subsidiarity. This principle is based on the positive assumption that society – its citizens and social communities – should develop their activities and that the state should help them and intervene when necessary. In this way, the principle of subsidiarity is formulated both in secular law and in the social doctrine of the Catholic Church. In the latter case, this is one of the key issues presented in the papal encyclicals.